2018
DOI: 10.1001/jamacardio.2018.1233
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Cardiovascular Outcomes With Masked Hypertension Defined by Home Blood Pressure Monitoring in a Japanese General Practice Population

Abstract: In the Japanese general practice population, masked hypertension defined by HBPM may be associated with an increased risk for stroke events. Use of HBPM may improve the assessment of BP-related risks and identify new therapeutic interventions aimed at preventing cardiovascular disease events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
3
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 48 publications
(73 reference statements)
4
49
3
6
Order By: Relevance
“…24 In an analysis of data from the J-HOP study of Japanese patients, the increased stroke risk associated with the presence of masked uncontrolled hypertension was comparable to that of sustained hypertension (clinic SBP ≥140 mm Hg and home SBP ≥135 mm Hg). 54 Home BP variability was greater in the Asia BP@Home study with a significant country/regional difference, even though home BP control status was better in the Asia BP@Home vs J-HOP studies.…”
Section: Discussionmentioning
confidence: 80%
“…24 In an analysis of data from the J-HOP study of Japanese patients, the increased stroke risk associated with the presence of masked uncontrolled hypertension was comparable to that of sustained hypertension (clinic SBP ≥140 mm Hg and home SBP ≥135 mm Hg). 54 Home BP variability was greater in the Asia BP@Home study with a significant country/regional difference, even though home BP control status was better in the Asia BP@Home vs J-HOP studies.…”
Section: Discussionmentioning
confidence: 80%
“…The increased stroke risk associated with masked hypertension was seen when the phenomenon was detected using ABPM and HBPM, ABPM only or HBPM only . Increased stroke risk in patients with masked hypertension was also documented in the J‐HOP study …”
Section: Masked Hypertension In Asiamentioning
confidence: 70%
“…Currently available evidence suggests that the cardiovascular risk associated with white‐coat hypertension in the absence of other coexisting risk factors is negligible . In the Japan Morning Surge‐Home Blood Pressure (J‐HOP) study, white‐coat hypertension detected using home blood pressure monitoring (HBPM) was not significantly associated with stroke risk over a median follow‐up duration of 3.9 years . Conversely, data from a population‐based study (also conducted in Japan) documented a significant independent association between white‐coat hypertension diagnosed based on elevated office BP and normal home or ambulatory BP and increased stroke risk .…”
Section: White‐coat Hypertension In Asiamentioning
confidence: 99%
“…A recent study also demonstrated that morning home BP was more reproducible and better correlated with vascular indices than ambulatory BP . To date, there have been five general practitioner‐based home BP cohort studies (Table ), including the HOMED‐BP (Hypertension Objective Treatment Based on Measurement by Electrical Devices of Blood Pressure) study, the J‐HOP (Japan Morning Surge‐Home Blood Pressure) study, and the HONEST (Home Blood Pressure Measurement With Olmesartan Naive Patients to Establish Standard Target Blood Pressure) study . All of these showed that morning home BP was a better predictor of cardiovascular events than office BP.…”
Section: Hope Asia Networkmentioning
confidence: 99%